Dolomitization and hydrotectonic model of burial dolomitization of the Furongian-Lower Ordovician carbonates in the Tazhong Uplift, central Tarim Basin, NW China: Implications from petrography and geochemistry. (August 2019) - Hu, Mingyi; Ngia, Ngong Roger; Gao, Da
Abstract: The nature of the dolomitizing fluids and genesis of the Furongian-Lower Ordovician dolomites and dolomite cements are interpreted on the basis of petrography, geochemistry (trace elements, REEs, O-C-Sr isotopes) and fluid inclusion microthermometry. These carbonate strata were deposited on a shallow marine platform in the Tazhong Uplift in central Tarim Basin and were extensively dolomitized. Based on field investigations and petrographic examination, two types of fabric-retentive dolomitic textures (dolomicrites (DM) and microbial dolomudstone (DMS)) and three types of fabric-obliterated dolomitic textures (very fine- to fine-crystalline planar-e(s) dolomite (RD1), fine- to medium-crystalline planar-e(s) dolomite (RD2) and medium- to coarse-crystalline nonplanar-a, planar-e(s) dolomite (RD3)) are identified. Two types of dolomite cements (medium- to coarse-crystalline dolomite cement (DC1) and coarse- to very coarse-crystalline saddle dolomite cement (DC2) are identified. The REE patterns of the analyzed dolomites and calcite cements are characterized using seawater normalization standard. The DC2 dolomite cement and later-stage calcite cement (LSCAL) display positive Europium anomalies (δEu) and positive Cerium anomalies (δCe). Whereas the DM, DMS, RD1, RD2, RD3 and early-stage calcite cement (ESCAL) samples display positive δCe, light REE (LREE) enrichment and negative δEu. The DM and DMS were formed through seawater flux and mesosaline brine derived from evaporative seawater during early-burial seepage-reflux dolomitization and microbial dolomitization, respectively. The preferential occurrence of RD1 along low-amplitude stylolites suggest that their formation may have linked to pressure dissolution by which Mg-ions were probably released for replacement dolomitization during late early-burial to early shallow-burial dolomitization. Moreover, the tightly packed and curved crystal faces of RD2 and RD3 with irregular overgrowth rims and increasing crystal sizes presumably resulted from the recrystallization and replacement upon the RD1 and/or from the cortical overgrowth and dissolution of remaining precursor limestones by the influx of dolomitizing fluids during late shallow-burial dolomitization. The average range of the homogenization temperatures ( Th ) of CD2 is 132.4 °C–198.7 °C; and mostly higher than the estimated ambient temperature (95 °C–150 °C) for the Furongian-Lower Ordovician strata, implying that the growth of DC2 in the study area was the result of hydrothermal dolomitization. The comparable isotopic (δ 18 O, δ 13 C and 87 Sr/ 86 Sr) values between RD2, RD3, DC1, DC2 dolomites and coeval Neoproterozoic to Early Phanerozoic seawater values, in addition to the relatively high Th and salinity levels in these dolomites, indicates that their dolomitizing fluid were derived from radiogenic 87 Sr-enrich coeval seawater during late shallow-burial dolomitization and hydrothermal dolomitization. The hydrotectonic driving model of burial dolomitization of the Furongian-Lower Ordovician carbonates in the Tazhong Uplift resulted from compressional tectonics that affected the Tarim Basin during Cambrian to Middle Ordovician and Late Ordovician period. This model is characterized by fluid flow in response to significant thermal heating, pressure-loading and enhanced fluid expulsion by squeezing, and the resultant higher-temperature Mg-rich connate waters and hydrothermal basinal brines are conveyed by convective-advective flows along permeable horizons, fractures and overthrust fault planes, resulting in extensive replacement dolomitization of carbonate materials and recrystallization of early formed dolomites; forming irregular networks of dolomites and calcite cements in the host carbonate rocks. Highlights: Dolomitizing fluids were coeval Lower Paleozoic seawater and hydrothermal basinal brines. Collision tectonics, thermal and hydrotectonic driving convective-advective fluid flow. Seepage-reflux, burial and hydrothermal dolomitization are proposed. Intercrystalline pores, vugs and fractures are the main types of porosity in the dolomites. Carbonate environments were restricted-open platform and platform margins.